1999
DOI: 10.1016/s1010-7940(99)00234-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin T release during coronary surgery using intermittent cross-clamp with fibrillation, on-pump and off-pump beating heart

Abstract: Coronary bypass grafting without aortic cross-clamping and without CPB offers superior myocardial protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 15 publications
3
25
1
5
Order By: Relevance
“…Pathophysiologically, this is reflected by an extended degree of inflammatory response [4] and myocardial injury [20,21], especially if the CPB run is prolonged [10]. The activation of numerous inflammatory mediators may compromise myocardial performance, particularly if the LV function is already severely impaired [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiologically, this is reflected by an extended degree of inflammatory response [4] and myocardial injury [20,21], especially if the CPB run is prolonged [10]. The activation of numerous inflammatory mediators may compromise myocardial performance, particularly if the LV function is already severely impaired [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…12,13,15,19,20 Early surgical outcomes were better in the on-pump beatingheart group in our study, and this result is consistent with those reported in several studies. [18][19][20][21] Postoperative LCOS ratios, perioperative infarction, new IABP insertion (for weaning from the CPB), and duration of inotropic support were significantly lower in the onpump beating-heart group than the conventional group. Postoperatively, intensive care unit and hospital stay as well as hospital costs decreased in the on-pump beatingheart group.…”
Section: Researchmentioning
confidence: 90%
“…Krejca and colleagues 18 found that troponin T levels were higher with conventional CABG than with on-or off-pump beating-heart techniques. Patients with left ventricular dysfunction may be unable to sustain an adequate intraoperative cardiac output during the beating-heart technique; hence, the theoretical need exists for mechanical support from a CPB circuit as a hybrid procedure.…”
Section: Researchmentioning
confidence: 99%
“…A similar benefit was seen in the surgical arm of the Guardian trial (6), in which peak cardiac enzyme levels were significantly lower in the subgroup receiving cariporide at an equivalent dose to that used in the present study. Although the release of cardiac enzymes and troponin reflect the effects of both ischemia and surgical trauma, there is evidence in the literature that postoperative levels correlate well with the severity of ischemic injury and clinical outcome (28,29).…”
Section: Discussionmentioning
confidence: 99%